Environmental changes during Mesolithic-Neolithic transition in Kuyavia Lakeland, Central Poland. (20th January 2023) - Makohonienko, Mirosław; Płóciennik, Mateusz; Papiernik, Piotr; Kittel, Piotr; Gałka, Mariusz; Mroczkowska, Agnieszka; Apolinarska, Karina; Okupny, Daniel; Panfil, Monika; Kotrys, Bartosz; Luoto, Tomi P.; Krąpiec, Marek; et al.
Abstract: The Wietrzychowice Cultural Park protects one of the last preserved megalithic barrows constructed by the Funnel Beaker Culture societies at the Kuyavia Lakeland (Central Poland). The nearby archaeological site at Śmieły located on the shore of Karaśnia Lake provided numerous Mesolithic and Neolithic remains such as flint artefacts, potsherds, arrowheads, and mammal bones with traces of human processing. The lake and peat sediments at the Śmieły site provided a unique opportunity to investigate man-environment relationships during the transition period from Mesolithic to Neolithic. The age-depth model for the deposits was based on five radiocarbon dates as well as archaeological artefacts. The multi-proxy study, including geochemistry, pollen, plant macrofossils, Mollusca, Cladocera and Chironomidae analyses, were conducted to recognize palaeoenvironmental changes between 7500 and 3500 BCE. Combining environmental and archaeological data, we attempt to distinguish between natural phenomena triggered by climate factors with those induced by human activity. The data indicated hydrological changes associated with natural factors: (1) the phase of aquatic ecosystem since 7500 to 5800 BCE, (2) the phase of water shallowing between 5800 and 4600 BCE, and (3) the development of alder fen in the lake shore zone since ca. 4600 BCE. Vegetation changes suggest early landscape transformations in Central Poland already due to the activity of Mesolithic societies. Fossil pollen and plant macroremains data combined with detailed map of modern soil distribution in the area allowed to identify pattern of vegetation distribution around the Mesolithic campsite. Neolithic discontinuity of habitation process between ca. 4600 and 4000 BCE (in the times of Brześć Kujawski Group of Lendyel Culture) can be associated with climate change resulting in Karaśnia Lake level lowering.